Impact of light-curing distance on the effectiveness of cure of bulk-fill resin-based composites - Rana Abdelbaset Diab; Adrian Ujin Yap; Maria Angela Garcia Gonzalez; Noor Azlin Yahya (Elsevier, 2021)
Objective: To investigate the effect of light-curing distance on the effectiveness of cure (EC) of bulk-fill resin-based composites (RBCs). Materials and methods: Two bulk-fill RBCs (a Tetric N-Ceram Bulk Fill (TN) and a Filtek Bulk Fill (FK)) are evaluated. Specimens (4 mm high) are cured for 20 s at different distances (0 mm (D0), 2 mm (D2), 4 mm (D4), 6 mm (D6) and 8 mm (D8)) and stored for 24 h in 100% relative humidity at 37 °C. The top and bottom surface hardness (SH) (n = 12) are assessed using a Knoop microhardness tester and the EC is calculated. The EC is characterized by the hardness ratio (HR) (mean bottom: top SH). An HR of 0.8 is used as the benchmark for an effective/adequate cure. Data are analyzed using one-way analysis of variance and Tukey's post hoc test (α = 0.05). Correlations between the top and bottom surfaces are examined using the Pearson correlation (α = 0.05). Results: For the TN, the HR at D8 is significantly lower than all other light-curing distances, while for the FK, it is significantly lower than D0 only. Conclusion: The effect of light-curing distance on the EC of bulk-fill RBCs is material dependent. Notwithstanding the light-curing distance, the EC of the FK and TN is below the threshold HR value of 0.8 when photopolymerized for 20 s in 4 mm increments in black opaque molds.